Distribution of Lipids in the Wall and Cytoplasmic Membrane Subfractions of the Cell Envelope of Escherichia coli - White, David A. (1972)
Cell wall and membrane subfractions of the cell envelope of Escherichia coli have been isolated by a procedure involving particle electrophoresis and sucrose gradient density centrifugation. The lipid content of each fraction has been investigated. The individual phospholipids of both fractions are quantitatively similar except that the proportion of lysophosphatidylethanolamine is greater in the wall than in the membrane. Fatty acid analysis of the phospholipids of each fraction revealed that the wall phospholipids contain a greater proportion of palmitic acid. Coenzyme Q is almost exclusively localized in the cell membrane.